2003
DOI: 10.1093/jn/133.2.411
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Ratio of Dietary Carbohydrate to Protein Improves Body Composition and Blood Lipid Profiles during Weight Loss in Adult Women

Abstract: Claims about the merits or risks of carbohydrate (CHO) vs. protein for weight loss diets are extensive, yet the ideal ratio of dietary carbohydrate to protein for adult health and weight management remains unknown. This study examined the efficacy of two weight loss diets with modified CHO/protein ratios to change body composition and blood lipids in adult women. Women (n = 24; 45 to 56 y old) with body mass indices >26 kg/m(2) were assigned to either a CHO Group consuming a diet with a CHO/protein ratio of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
371
7
21

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(428 citation statements)
references
References 36 publications
26
371
7
21
Order By: Relevance
“…High-protein (HP) diets have been shown to cause weight loss by inducing longer postprandial satiety and increase dietary thermogenesis that led to a lower subsequent energy intake (Johnston et al, 2002;Halton and Hu, 2004). In obese and diabetic individuals, a higher utilization of fat reserves and improved glucose homeostasis was reported while subjected to diets containing higher protein contents (Farnsworth et al, 2003;Layman et al, 2003). Similar results were obtained in rats fed HP diets with reduced carbohydrate content (Jean et al, 2001; -E-mail: metges@fbn-dummerstorf.de Lacroix et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…High-protein (HP) diets have been shown to cause weight loss by inducing longer postprandial satiety and increase dietary thermogenesis that led to a lower subsequent energy intake (Johnston et al, 2002;Halton and Hu, 2004). In obese and diabetic individuals, a higher utilization of fat reserves and improved glucose homeostasis was reported while subjected to diets containing higher protein contents (Farnsworth et al, 2003;Layman et al, 2003). Similar results were obtained in rats fed HP diets with reduced carbohydrate content (Jean et al, 2001; -E-mail: metges@fbn-dummerstorf.de Lacroix et al, 2004).…”
Section: Introductionmentioning
confidence: 75%
“…15 Smaller lean mass losses are observed following energy-controlled, high-protein (HP) weight loss diets. 14,16 It is unclear whether these outcomes are affected by the source of protein. The impact of HP diets on other safety markers requires demonstration.…”
Section: Introductionmentioning
confidence: 99%
“…Several short-term, randomised, controlled studies (≤6 months duration) have shown that the replacement of some dietary carbohydrate with protein in low-fat diets (≤30%) enhances weight loss [7], is associated with favourable changes in body composition [7,8,9] and exerts beneficial effects on CVD risk factors, including insulin sensitivity [8], glycaemic control [10,11] and lipid profile [8,9,12]. While these diets may offer modest short-term metabolic advantages, to date, there are no long-term clinical trials of their long-term efficacy, safety and acceptability compared to conventional low-fat, high-carbohydrate diets in persons with Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%